Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1557/proc-0911-b01-05
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Dislocation Behavior during Bulk Crystal Growth of SiC

Abstract: Dislocation behavior during physical vapor transport (PVT) growth of silicon carbide (SiC) single crystals has been investigated by defect selective etching and transmission electron microscopy (TEM). It was found that foreign polytype inclusions introduced a high density of basal plane dislocations at the polytype boundary, while in the polytype-transformed areas of the crystal, the density of medium size hexagonal etch pits due to threading screw dislocations was significantly reduced, indicating that the po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…However, some dislocations disappeared or emerged, which can be explained by inter-conversion between threading and basal plane dislocations. TEM studies by Ohtani et al [10] showed some TEDs converted into BPDs during PVT growth of SiC. Nakamura et al [11] suggested that all types of threading and basal plane dislocations are capable to combine, dissociate and convert from one type into another.…”
Section: Propagation Of Threading Dislocations During Sic Crystal Growthmentioning
confidence: 99%
“…However, some dislocations disappeared or emerged, which can be explained by inter-conversion between threading and basal plane dislocations. TEM studies by Ohtani et al [10] showed some TEDs converted into BPDs during PVT growth of SiC. Nakamura et al [11] suggested that all types of threading and basal plane dislocations are capable to combine, dissociate and convert from one type into another.…”
Section: Propagation Of Threading Dislocations During Sic Crystal Growthmentioning
confidence: 99%
“…The experimental measurement of dislocation density typically covers a range from a fraction of millimeter to a few centimeters, which corresponds to the region with steady slope in the simulation (10 2 to 10 6 steps). These differences may explain the discrepancies reported in the literature [7]. Each step in the calculation corresponds to the increase in the crystal thickness that allows a threading dislocation to transverse a maximum distance of D m .…”
Section: Monte-carlo Simulationsmentioning
confidence: 97%
“…CONTROLLED CHANGE IN THE POLYTYPE DURING GROWTH Technological parameters of the growth process can give rise both to the appearance of polytype inclusions and to a complete change in the growing polytype. It is known that transformation of the polytype leads to a stop in the propagation of threading screw dislocations already present in the crystal by varying the defect structure in the ingot [11,2]. In addition, a programmed change in the polytype can basically form (on the basis of silicon carbide) so-called heteropolytype compositions, i.e., unstressed epitaxial structures, including those with a two-dimensional electron gas [57,58].…”
Section: Inclusion Of the 15r Polytypementioning
confidence: 99%
“…In particular, cracking, the appearance of regions with a high density of micropores (penetrating extended defects with a hollow core) and dislocations [10,11] are from time to time observed at the boundaries of polytype inclusions. Thus, prevention of the appearance of polytype inclusions in SiC ingots is a priority tasks in the technology of this material.…”
Section: Introductionmentioning
confidence: 99%